A Study Protocol for an Open-Label Feasibility Treatment Trial of Visual Snow Syndrome With Transcranial Magnetic Stimulation - Grande, Marissa; Lattanzio, Lucas; Buard, Isabelle; McKendrick, Allison M.; Chan, Yu Man; Pelak, Victoria S. (Frontiers in Neurology, 2021)
Background: Visual Snow (VS) syndrome is believed to be due to aberrant central visual processing. Positron Emission Tomography (PET) brain imaging and visual evoked potential studies provide evidence for excessive neuronal activity in the medial temporal lobe, specifically the lingual gyrus, and suggest the VS syndrome is a hyperexcitability syndrome. These data provide the basis for consideration of repetitive transcranial magnetic stimulation (rTMS) as a potential treatment for the VS syndrome. Objective: To publish the study protocol for a pilot study underway at the University of Colorado School of Medicine to investigate the use of rTMS intervention to improve symptoms and visual dysfunction associated with VS. The study aims to determine the adverse events and drop-out rate, evaluate performance of outcome measures, including a novel VS symptom scale, and describe changes in outcomes associated with treatment. Methods and Design: Up to 10 participants meeting criteria for VS syndrome, age 19–65 years, will undergo an open-label intervention consisting of 10 rTMS sessions, occurring 5 days a week over a 2-week period. Participants will complete pre-treatment and post-treatment assessments that include: the Colorado Visual Snow Scale (CVSS), the National Eye Institute Visual Functional Questionnaire—25 (VFQ-25), the General Anxiety Disorder—7 scale (GAD-7), and three psychophysical visual processing tasks. Discussion: Knowledge gained from this pilot study will inform future study planning and provide valuable lessons for future investigation of rTMS for the VS syndrome. An overview of study proceedings thus far demonstrates recruitment challenges associated with the COVID-19 pandemic, and additional challenges that are unique to the VS syndrome and to treatment schedules associated with TMS. Registration: This study has been approved by the Colorado Multiple Institutional Review Board. ClinicalTrials.gov Identifier: NCT04925232.